2016
DOI: 10.22159/ijpps.2016v8s2.15223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indonesian Velvet Bean Extract on the Fertility of Albino Male Mice

Abstract: Objective: This research aims to determine the dose of Indonesian velvet bean (Mucuna pruriens) extract which has significant effect on the ferlitity mice (concentration, motility and morphology of mice sperm). The extract is expected to become an alternative infertility herbal medicine relatively more secure and affordable replacing synthetic hormonal drugs which tend to have negative effects. Methods:The seed was taken from Yogyakarta Indonesia. Fertility test was done to fertile adult male albino mice 12 w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It indicated that higher number of sperm in A2 and A3 also gave a stronger spermatogenesis activity, whereas ZS and VBE have aphrodisiac content to increase the number of sperm. This is in line with the general knowledge that ZS can increase the number of sperm stem cells (Sedigh et al, 2016) and VBE can increase the number of sperm with stimulating the hormones of mice (Sardjono et al, 2016).…”
Section: The Number Of Spermsupporting
confidence: 87%
See 3 more Smart Citations
“…It indicated that higher number of sperm in A2 and A3 also gave a stronger spermatogenesis activity, whereas ZS and VBE have aphrodisiac content to increase the number of sperm. This is in line with the general knowledge that ZS can increase the number of sperm stem cells (Sedigh et al, 2016) and VBE can increase the number of sperm with stimulating the hormones of mice (Sardjono et al, 2016).…”
Section: The Number Of Spermsupporting
confidence: 87%
“…Abnormal sperm includes abnormality such as broken, detached and thin head; broken, crooked and droplet cytoplasm middle part or broke, crooked and coil tail. The observation used a microscope of 400x magnifications (Henderson and Robaire, 2005;Sardjono et al, 2016).…”
Section: The Viability Of Spermmentioning
confidence: 99%
See 2 more Smart Citations
“…In India, the prevalence of infertility in men is increasing steadily and it has reached to such alarming levels that its incidence may affect the male population in future. The incidence cannot be ignored, therefore a detailed study involving the sperm count and hormonal profile especially FSH, LH, and testosterone concentration is an urgent necessity to ascertain the fertility problems in men [14]. Unfortunately, this study is poorly documented in India; therefore, this study can be considered as a step toward evaluating the GnRH level in infertile young male in Indian population.…”
Section: Introductionmentioning
confidence: 99%